Correlation between Neck Circumference and Other Anthropometric Measurements in Eight Latin American Countries. Results from ELANS Study - Reyna Liria-Domínguez (MDPI AG, 2021)
Neck circumference (NC) is being used to identify the risk of chronic diseases. There is a high prevalence of overweight and obesity in Latin America, and neck circumference is a simple and practical measurement to assess this, especially in primary health centers. We analyzed the correlation between the NC anthropometric indicator and other anthropometric measurements such as BMI and waist circumference (WC) in eight Latin American cities. We applied Pearson’s correlation to identify the correlate NC with the other anthropometric variables stratified by sex; the sensitivity (Se) and specificity (Sp) by sex were evaluated according to the cut-off established with the Youden Index. The strongest correlations between NC and WC were found when stratified by sex (women: r = 0.71; men: r = 0.69, respectively) followed by the correlation between NC and BMI (r = 0.65, both sex). NC cut-off points of 39.0 cm in men and 32.9 cm in women identified those individuals with an increased WC and 39.8 and 33.7 cm, respectively, for a substantial increase in WC. For BMI ≥ 25.0 kg/m2 for men, the cut-off point was 37.5 cm, and for women, it was 33.1 cm, and for BMI ≥ 30 kg/m2, the cut-off points were 39.2 and 34.2 cm, for men and women, respectively. Conclusion: NC proved to be a useful, practical, and inexpensive tool that can be used to identify, evaluate, and monitor overweight and obese individuals.